Lignin linked to slow biodegradability of urea-crosslinked starch in an anaerobic soil environment - Majeed, Z. (European Polymer Federation, 2018)
For slowing fast solubility and increasing the period of urea's release in soil, urea-crosslinked starch (UcS) was prepared and applied as a slow release fertilizer. The higher environmental biodegradability of UcS is a major drawback for slow release of urea yet it provides an important challenge for large scale production and application on anaerobic farm lands. Hence, in order to reduce biodegradability of UcS, impregnation of UcS with 5-20 wt of lignin is proposed. Lignin impregnated UcS was buried for a maximum period of 28-64 days under a constructed anaerobic soil environment. Hill's model predicted that mineralization of UcS by lignin would be reduced by 5.48. Microbial growth on UcS was inhibited by lignin at the rate of 0.84 day-1. The Î±-amylase activity was retarded in response to UcS impregnation with lignin at the rate of 810.94 Î¼g h-1 g-1 soil. Lignin also showed improvement in half-life of UcS up to 0.51 days. This work concluded that lignin impregnation was an efficient approach for improvement of UcS through increasing resistance against natural biodegraders. Â© 2018 Walter de Gruyter GmbH, Berlin/Boston 2018.